2022
DOI: 10.1021/acschemneuro.2c00209
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms behind the Fibrillation and Toxicity of Insulin Fibrils on Neuron Cells by Engineered Curcumin Analogs

Abstract: Among foods, the use of plant derivatives as promising drugs and/or excipients has been considered from various perspectives. In the present study, curcumin, which is one of the most important plant derivatives for biological uses, and four curcumin-based pyrido­[2,3-d]­pyrimidine analogs (C2-C5) were used for investigating the mechanism of insulin fibrillation and evaluating the cytotoxicity of insulin fibrils. The synthesized analogs differed in terms of hydrophobicity and electrostatic charge. The analogs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…Additionally, other studies have mentioned the binding of amyloids on cells by their electrostatic charge. , The positive charge present in amyloids may lead to their better binding to cells with a negative charge, but this mechanism does not seem to be universal; in the present study, despite the negative charge of HSA-F (Figure ), we witnessed the strong attachment of cells to the scaffold (Figures and ). However, in a study that we had done before, we found that the positive charge of the monomers that make amyloids can lead to a delay in their fibrillation process and general structure . The lingering question pertains to what constituents present on the surface of amyloids evoke favorable responses from cells.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Additionally, other studies have mentioned the binding of amyloids on cells by their electrostatic charge. , The positive charge present in amyloids may lead to their better binding to cells with a negative charge, but this mechanism does not seem to be universal; in the present study, despite the negative charge of HSA-F (Figure ), we witnessed the strong attachment of cells to the scaffold (Figures and ). However, in a study that we had done before, we found that the positive charge of the monomers that make amyloids can lead to a delay in their fibrillation process and general structure . The lingering question pertains to what constituents present on the surface of amyloids evoke favorable responses from cells.…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, to measure the thermal stability of HSA-F, the investigation of the secondary structures by ATR-FTIR in the dry state and Raman spectroscopy in the water-soluble state was used (Figure D). To investigate the secondary structures of proteins by FTIR spectra, the amide-II region, which covers the wavenumber range between 1600 and 1700 cm –1 , is of great importance. ,, Compared to the HSA monomer, which contains 29.5% α-helix structure, HSA-F has undergone α-helix to β-sheet transition to contain 40.3% β-sheet. After HSA-F was incubated at 140 °C for 3 h, it was seen that part of the helix and β-sheet turned into extended chain structures (Table S2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations